UMKM GOING UP A LEVEL: Simple Financial Management, Cost of Goods Manufactured (COGM), and Profit Strategy - Frilla Gunariah; Gunarto Wardjono; Kus Indiyah; Patriandari; Sari Mujiani (Britain International for Academic Research (BIAR) Publisher, 2026)
This Community Service Program aimed to improve the capacity of Micro, Small, and Medium Enterprises (MSMEs) in managing business finances through understanding simple financial management, Cost of Goods Manufactured (COGM), and profit improvement strategies. The activity was conducted in Bantar Agung Village, Majalengka Regency, West Java on May 8–9, 2026 at the Multipurpose Hall of the Bantar Agung Village Office. The program was attended by 11 participants from local MSME communities. The activity was organized by lecturers from Politeknik Jakarta Internasional, STAI Sebelas April Sumedang, and Universitas Islam As-Syafi'iyah in collaboration with the Bantar Agung Village Government. The implementation methods included lectures, interactive discussions, simulations of production cost calculations, and mentoring on simple financial management. The results showed an increase in participants’ understanding of recording business finances, accurately calculating production costs, and determining pricing and profit strategies more effectively. This program is expected to improve the managerial capabilities of village MSMEs so that their businesses can develop sustainably and become more competitive.